Attitudes of Generation X and Y towards Buying Second-hand Dwellings - Sornatthakit, Verawan; Pongpattrachai, Dichapong (KKBS Journal of Business Administration and Accountancy, 2024)
Currently, prices of new real estate developments rapidly increase due to the sharp escalation in construction material costs and land prices. Second-hand dwellings have become an alternative to current generations. Secondhand property markets have grown continuously. This research has used theory of consumption values to study attitudes of Generation X and Generation Y (Gen X and Gen Y) toward second-hand dwellings. Mixed methods of qualitative and quantitative research approaches have been used to collect and analyze data. The results show that function value, epistemic value, and conditional value are significantly associated with attitudes toward second-hand dwellings on overall. When we considered the data of Gen X and Gen Y separately, the conditional value is significantly associated with Gen X’s attitudes but not Gen Y’s attitudes. This shows that Gen X may buy second-hand dwellings subject to more conditions than those of Gen Y.